2015
DOI: 10.1007/s00167-015-3731-4
|View full text |Cite
|
Sign up to set email alerts
|

Prospective multifactorial analysis of preseason risk factors for shoulder and elbow injuries in high school baseball pitchers

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
229
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(241 citation statements)
references
References 41 publications
(89 reference statements)
2
229
2
Order By: Relevance
“…A single end of season questionnaire was used in three studies 34–36. One of these studies also used self-report at medical check-ups 34. Serial administration of standardised questionnaires was used in two studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A single end of season questionnaire was used in three studies 34–36. One of these studies also used self-report at medical check-ups 34. Serial administration of standardised questionnaires was used in two studies.…”
Section: Resultsmentioning
confidence: 99%
“…One study classified shoulder pain as pain lasting at least 2 weeks, but not necessarily requiring withdrawal from sport 36. One study classified shoulder pain as requiring greater than 7 days of withdrawal from participation 34. One study administered 15 questionnaires and an average score called the Cumulative Severity Score (CSS) was calculated 24.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among high school pitchers, Shitara et al . have shown that risk factors for preseason injury include a low dominant to nondominant side prone external rotation ratio and decreased dominant side passive 90° abducted internal rotation range of motion (ROM)1. Among high school baseball and softball players, risk factors have been shown to include shoulder internal rotation and horizontal adduction ROM deficits2.…”
mentioning
confidence: 99%